Streaming, Scrolling, and Spending: How Social Media Drives Impulse Buying in Gen Z (Evidence From Netflix’s Subscribers) - Aida Vitria; Amalia Wahyuni; Rizka Zulfikar (International Journal of Science, Technology & Management, 2026)
The study aims to investigate the moderating efect of social media in relationship of hedonic motives, impulsive tendency, and impulsive buying decision decision among Gen Z in subscription to Netflix Streaming Services. These research was conducted because the lact of research on the role of social media moderation and the mediating role of impulsive buying tendency is still rarely carried out, especially in terms of examining the factors that influence gen Y in choosing digital services such as TV streaming. These study used Gen Z who has been a subscriber of Netflix for 1 year in South Kalimantan as sample total of 187 respondents with purposive sampling as sampling method. The study used a quantitative research design and collected data through a survey questionnaire and analyzed with the Structural Equation Model – Partial Least Squares (SEM-PLS). The results of this study found that hedonic motives and impulsive buying tendencies had an impact on Gen Z's impulse buying decision to choose Netflix as a digital streaming service. While social media moderated hedonic motives, this study also found that impulsive buying tendency affected mediated hedonic motives and impulse buying decisions. These results have a practical contribution and have scientific implications that can help better understand consumer behavior in the context of digital services, especially on TV streaming services. This study also led to further research in this field and contributed to the literature on social media, hedonic motives, impulsive decision-making, and impulsive tendency.